Factibilidad para el Desarrollo de un centro de arbitraje y mediación en el Cantón Bolívar. - Barre Basurto, Ramón Clemente (2010)
The investigation to stady it shows the feasibility to develop the center of meditation and arbitration in the city of Calceta real realizing surveys in the tree parishes of this city to see if the citizen have acceptance in the center of creation. We in consiteration the general objective the determine feasibility to constitute a center meditatation and arbitration that faclisitale the processes of civil causes in the city of Bolivar , for that to accomplish the estabitsh the treespec objectives to help the accomplishment the general objective , beliving in the study of market for development of one center of meditation and arbitration evaluating the effect of economic of honors of the arbitratos and mediators and organized administhation of the creatives center meditation and arbitration that agree with the regulation and the statutes of the law. Realing so the ensus of 11 questions only for the citizens of particular city withen that only 39.20% answered to 375 people who live in the parishes Quiroga and membrillo and only 61.80% answered to 379 total population of the city of bolivar .during the process of data we used tables statistics and tha shawn the results by means graphs estadisticos afferrealizing the respected analysis of result. Looking at the level of result is of thr city the bolivarenses one in 53% kwaw the definition of mediation and arbitration therefore and only 61 %agree that exsist as center medidation and arbitration and 100% they think that the creation of the center will be visits of the citizens that go to cocurt and to the comisaria , the realized that only 72% go every year and 69% that reacieve at the moment of of resdveme of a conflict cause by a civilian in this place is wrorg . Evaluaty the economic effect of the honorary mediators and arbitrators, we conclute that the terifs estalishet defend on avery center of mediation and the porcentaje of the mediators and arbritrators are seprated and ultimathey is mach highor we agree in comparasing withen afher center of mediators and arbitrators could get to create an administrative organization to create a new center of mediation and arbitration.